Facial retention ligaments: a clinical considerations review (Research, Society and Development, 2022)
The advancement of techniques and technologies used in procedures of facial rejuvenation, several structures of the face must be highlighted in order to obtain clinical success such as the facial retaining ligaments (FRL). It is known that the classic characteristics of the aged face imply in the LRF, intimate relationship of the ligaments with the cutaneous tissues can be modified from structural and functional changes. Furthermore, the understanding of the LRF must be considered by the professional as targets of clinical action, as a way to increase the effectiveness, naturalness of the results and patient satisfaction. In order to understand the clinical importance of the facial retaining ligaments, 29 articles were used in this research, as a form of literary review. According to the results found, the understanding of the physiological changes over time and their clinical repercussion demonstrate that the facial retaining ligaments are of fundamental importance for the decision of the technique and protocol in rejuvenating procedures.